1998
DOI: 10.1046/j.1365-2648.1998.00768.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of computer software in the analysis of qualitative data: efficient clerk, research assistant or Trojan horse?

Abstract: In the last 15 years there has been a proliferation of computer software packages designed to facilitate qualitative data analysis. The programs can be classified, according to function, into a number of broad categories such as: text retrieval; text base management; coding and retrieval; code-based theory building; and conceptual-network building. The programs vary enormously in the extent to which they can facilitate the diverse analytical processes involved. The decision to use computer software to aid anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 32 publications
0
36
0
8
Order By: Relevance
“…This is an important distinction, as reliance on computer analysis of data has a significant potential to produce erroneous results. The literature suggests that although software programs may save time, it is not clear if this adds to the analysis or detracts from it by distancing the researcher from the data through the mediation of computer, as the familiarity with the data engendered through repeated handling, reading and re-reading is an integral part of the analytical process [42,44,45]. Although more time consuming and a bit old fashioned, these authors still prefer hand coding as we feel it provides a more organic emersion and understanding of the data.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…This is an important distinction, as reliance on computer analysis of data has a significant potential to produce erroneous results. The literature suggests that although software programs may save time, it is not clear if this adds to the analysis or detracts from it by distancing the researcher from the data through the mediation of computer, as the familiarity with the data engendered through repeated handling, reading and re-reading is an integral part of the analytical process [42,44,45]. Although more time consuming and a bit old fashioned, these authors still prefer hand coding as we feel it provides a more organic emersion and understanding of the data.…”
Section: Analysis Of Datamentioning
confidence: 99%
“…I used MaxQDA 12 , a computer programme designed to facilitate coding. Discussions about Computer Assisted Qualitative Data Analysis Systems (CAQDAS) question if CAQDAS improves or harms the quality of the analysis (Fielding & Lee, 1998;Kelle, 1997;Marshall, 2002;Morison & Moir, 1998). Opponents fear computers bring positivist assumptions and a lack of creativity, whereas proponents celebrate the rigour and speed that computers add to the coding process.…”
Section: Discussionmentioning
confidence: 99%
“…Waldinger et al (1990) identified the migrant experience of only low-paid jobs and discrimination as principal factors that compel migrants to self-employment. Migrant small business owners often face challenging experiences in business management and finance (Collins, 2003;Gaskill, Auken, Howard, & Manning, 1993;Morrison & Moir, 1998;Ram & Deakins, 1996).…”
Section: Labour Disadvantage Theorymentioning
confidence: 99%